Hubungan Budaya Keselamatan dengan Ketepatan Identifikasi Pasien di Rumah Sakit Islam Sultan Agung - Jundi Anas Zulfikar; Muh. Abdurrouf; Dyah Wiji Puspita Sari (Journal of Health, Medical, and Psychological Studies, 2026)
Patient misidentification constitutes a fundamental and preventable risk in healthcare delivery, which can be minimized through the establishment of a strong safety culture. This study aimed to analyze the relationship between safety culture and the accuracy of patient identification at Rumah Sakit Islam Sultan Agung Semarang. The research employed a quantitative design with a cross-sectional approach. The sample consisted of 94 staff nurses working in inpatient wards, selected using a total sampling technique. Data were collected through questionnaires and direct observation, and subsequently analyzed using the Spearman Rank correlation test. The findings revealed that most nurses demonstrated a moderate level of safety culture (40.4%) and good patient identification accuracy (43.6%). Statistical analysis indicated a significant but weak correlation between safety culture and the accuracy of patient identification (p-value = 0.043; r = 0.209). Safety culture contributes positively to identification accuracy, although it is not the sole determining factor. It is therefore recommended that hospitals strengthen periodic audits and develop non-punitive incident reporting systems to optimize compliance.